Direct and Indirect Real Estate Investment Performance – Data from Bulgaria, the Eurozone, the UK and the US - Blagovest Iliev (Business & Management Compass, 2025)
There is ample research on the similarities and differences between direct and indirect investment in real estate. Some claim that both behave similarly, offer similar investment performance and diversification benefits to investors, while others are in the view that there are differences and the two types of investments in real estate cannot be treated as substitutes. This paper analyses the capital return and risk performance of direct investment in residential properties and indirect investment in real estate on the stock exchange in Bulgaria. The results are compared to other markets in the eurozone, the UK and the US. Overall direct investments in the residential market appear preferable for the risk averse investor compared to indirect investments in REITs especially in adverse economic conditions. The average return in the residential market is greater than the return from REITs in the eurozone and the UK and almost equal to it in Bulgaria and the US. However, the volatility is significantly lower than the volatility of REITs returns in all markets. There is significant improvement in the volatility of REITs in more stable economic conditions but it is not enough to outperform direct investments on risk adjusted basis.